Connect with experts and get insightful answers on IDNLearn.com. Our platform provides trustworthy answers to help you make informed decisions quickly and easily.
Sagot :
To determine the result of the function [tex]\( \text{fun1}(x, y) \)[/tex] given [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \)[/tex], let's work through the function step by step:
1. Initial Call: The function is initially called with [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \)[/tex].
2. First Iteration: Check if [tex]\( x == 0 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 5) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(5 - 1, 5 + 2) = \text{fun1}(4, 7) \][/tex]
3. Second Iteration: Now, the function is called with [tex]\( x = 4 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 4) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(4 - 1, 4 + 7) = \text{fun1}(3, 11) \][/tex]
4. Third Iteration: Now, the function is called with [tex]\( x = 3 \)[/tex] and [tex]\( y = 11 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 3) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(3 - 1, 3 + 11) = \text{fun1}(2, 14) \][/tex]
5. Fourth Iteration: Now, the function is called with [tex]\( x = 2 \)[/tex] and [tex]\( y = 14 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 2) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(2 - 1, 2 + 14) = \text{fun1}(1, 16) \][/tex]
6. Fifth Iteration: Now, the function is called with [tex]\( x = 1 \)[/tex] and [tex]\( y = 16 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 1) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(1 - 1, 1 + 16) = \text{fun1}(0, 17) \][/tex]
7. Final Iteration: Now, the function is called with [tex]\( x = 0 \)[/tex] and [tex]\( y = 17 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (True because } x = 0) \][/tex]
Since [tex]\( x == 0 \)[/tex], the function returns [tex]\( y \)[/tex]:
[tex]\[ \text{return } y = 17 \][/tex]
Thus, the function [tex]\( \text{fun1}(5, 2) \)[/tex] returns [tex]\(\boxed{17}\)[/tex].
1. Initial Call: The function is initially called with [tex]\( x = 5 \)[/tex] and [tex]\( y = 2 \)[/tex].
2. First Iteration: Check if [tex]\( x == 0 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 5) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(5 - 1, 5 + 2) = \text{fun1}(4, 7) \][/tex]
3. Second Iteration: Now, the function is called with [tex]\( x = 4 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 4) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(4 - 1, 4 + 7) = \text{fun1}(3, 11) \][/tex]
4. Third Iteration: Now, the function is called with [tex]\( x = 3 \)[/tex] and [tex]\( y = 11 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 3) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(3 - 1, 3 + 11) = \text{fun1}(2, 14) \][/tex]
5. Fourth Iteration: Now, the function is called with [tex]\( x = 2 \)[/tex] and [tex]\( y = 14 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 2) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(2 - 1, 2 + 14) = \text{fun1}(1, 16) \][/tex]
6. Fifth Iteration: Now, the function is called with [tex]\( x = 1 \)[/tex] and [tex]\( y = 16 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (False because } x = 1) \][/tex]
Since [tex]\( x \neq 0 \)[/tex], the function returns [tex]\( \text{fun1}(x - 1, x + y) \)[/tex]:
[tex]\[ \text{fun1}(1 - 1, 1 + 16) = \text{fun1}(0, 17) \][/tex]
7. Final Iteration: Now, the function is called with [tex]\( x = 0 \)[/tex] and [tex]\( y = 17 \)[/tex]:
[tex]\[ \text{if } x == 0 \text{; (True because } x = 0) \][/tex]
Since [tex]\( x == 0 \)[/tex], the function returns [tex]\( y \)[/tex]:
[tex]\[ \text{return } y = 17 \][/tex]
Thus, the function [tex]\( \text{fun1}(5, 2) \)[/tex] returns [tex]\(\boxed{17}\)[/tex].
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. IDNLearn.com is committed to your satisfaction. Thank you for visiting, and see you next time for more helpful answers.